PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT VICTORY CHINGLUH INDONESIA DI KABUPATEN TANGERANG - Deandra Sasi Raya Mahardika; Eko Trianto; Bambang Mardisentosa (MANAJEMEN, 2025)
This study aims to analyze the effect of leadership style, motivation, and work environment on employee performance at PT Victory Chingluh Indonesia, Tangerang Regency. Using a quantitative approach and survey method, primary data was collected through a Likert scale questionnaire from 100 respondents selected by random sampling. Data analysis was performed using SPSS 25, which included validity and reliability tests, classical assumptions, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination. The results showed that partially, leadership style (t-count 2.362 > t-table 1.984), motivation (t-count 2.864 > t-table 1.984), and work environment (t-count 5.301 > t-table 1.984) each have a positive and significant effect on employee performance at a significance level of < 0.05. Additionally, the F test results indicate that simultaneously, the three independent variables also have a significant effect on employee performance (Fcount 24.008 > Ftable 2.699) with a significance level of 0.000. Thus, it can be concluded that leadership style, motivation, and work environment are important factors that influence employee performance in the company.